Diversity Of Insect Pests In Rice Plant (Oryza Sativa L) in The Rice Fields Of South Kualuh District, North Labuhanbatu - Melfa Aisyah Hutasuhut; Kartika Manalu; Icha Aurelia Ahmad (Publisher Cv. Inara, 2021)
Eradicating rice pests in South Kualuh is difficult to do optimally, because most farmers do not understand the types of pests that attack their rice plants. The objective of this study was to obtain information about the type of pest insects in rice plants and to find out the diversity index of insect pests in rice plants. This research was conducted using trap method and collection of insects was done using a insect net. Observation data was analised using Shanon Wiener (H) diversity / diversity index. The result showed 13 types of pest insects which belongs to 10 families. That is Tettigonia sp.(Linnaeus, 1758), Sogatella furcifera (Horváth, 1899), Nephotettix virescens (Distant, 1908), Cofana spectra (Distant, 1908), Atractomorpha crenulata (Fabricius, 1793), Erotides sp.(Laporte, 1836), Leptocorisa acuta (Thunberg, 1783), Aulacophora indica (Gmelin, 1790), Chrysochus cobaltinus (LeConte, 1857), Silba capsicarum (McAlpine, 1956), Hercostomus germanus (Wiedemann, 1817), Cnaphalocrosis medinalis (Guenée, 1854), Scirpophaga incertulas (Walker, 1863). The diversity index of rice pest insects was categorized as moderate with a value of 2,35 and a dominance index of 0,108. This value indicates that the distribution of species is evenly distributed so that no insect species dominates in the area.